Global Citizenship Education and the National Education Policy 2020 Some Insights - Nikalje, Varada M (JOURNAL OF INDIAN EDUCATION, 2022)
It is being increasingly recognised across the world that addressing challenges to peace, and human and fundamental rights is important for the stability of societies. This requires increased levels of dialogue and cooperation among countries which will result in mutual benefit. It is also being recognised that the role of education in building just and peaceful societies and trust in institutions cannot be underestimated. This is particularly true when such learning begins at a young age and is reinforced throughout the educational trajectory in school. This is achievable through a combination of character attributes, such as being respectful, honest, helpful, and above all, developing the ability to listen. These traits are learnt over time. As the world is becoming increasingly interconnected, Global Citizenship Education (GCED), a response to contemporary global challenges that empowers learners to become aware of and understand global issues and to become active promoters of more peaceful, and sustainable societies, has become a matter of interest to educators. Indeed, the education policy of many countries has included GCED in their curricula. The National Education Policy of India, released on 29 July 2020, envisages many changes in education. One of them is the inclusion and integration of the concept of GCED, which resonates with the Indian concept of Vasudhaiva Kutumbakam, meaning, ‘the world is one family’. This paper examines GCED in the context of the New Education Policy at school and higher education levels.